Perancangan Aplikasi Penjualan Rumah dengan Augmented Reality - Nanito; Pastima Simanjuntak (Computer Science and Industrial Engineering, 2024)
growth and evolution of the world of technology is increasing rapidly, especially in computer and smartphone technology which is no longer for digging up information but has utilized technology to enter the business world in the form of applications such as virtual enchancement. AR is a merges of the future physical then digital worlds by using 3D objects that can be designed with supporting software are useful for designing house as three-dimensional object that are used by property businesses in house sales to make it easier for eachother to interact where seller still sell manually by distributing several brochures and buyers lack the time to visit the location on person. the reason of this ponder is to plan home sales apps that is useful for a lot facilitating interactions between home sellers and buyers. In this research, several house designs were made using sketchup and then using unity to connect to the display and included in unity to create an application in the form of function buttons to make it easier to use and combine 3D objects with markers. Based on the designed test, the application can function and display 3D objects correctly.